If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x = -4 + (4x + -1) Reorder the terms: 3x = -4 + (-1 + 4x) Remove parenthesis around (-1 + 4x) 3x = -4 + -1 + 4x Combine like terms: -4 + -1 = -5 3x = -5 + 4x Solving 3x = -5 + 4x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-4x' to each side of the equation. 3x + -4x = -5 + 4x + -4x Combine like terms: 3x + -4x = -1x -1x = -5 + 4x + -4x Combine like terms: 4x + -4x = 0 -1x = -5 + 0 -1x = -5 Divide each side by '-1'. x = 5 Simplifying x = 5
| -1/2m-3=9 | | A=3.14r | | 0.25y+19/2 | | 3y=702 | | 1/4y+91/2 | | 12x^2+9x^2=0 | | (cos)x=1 | | 1/4+4/8 | | 3-2-4-5= | | 12x-19=10x+20 | | 20+4y+y=180 | | 2x=6x-16 | | x+105=80+2x | | (ln(y))=2t+4 | | ln(y)=2t+4 | | lny=2t+4 | | 180-(x+105)+2x+80=180 | | 6h=5/7 | | 2x+9=-5-16 | | 21/2+131/10 | | b/3+2=7 | | 8n-1=19 | | y^2=4y+9 | | 3(2x+8)=60 | | p-6.9=7.47 | | 4+5u=-16 | | 8x-1=49 | | 6p=3/4 | | 2x+9=-5x-16 | | 12/5p=48 | | -3x-8=-14 | | 3(t-1)=33 |